Analysis of Work Facilities and Training on Employee Performance with Work Motivation as a Mediating Variable at the National Narcotics Agency North Sumatra Province - Lisa Fitria; Kiki Farida Ferine; Muhammad Isa Indrawan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is a strategic factor in supporting the effectiveness of task implementation in public institutions, including the North Sumatra Provincial National Narcotics Agency (BNN Provinsi Sumut). This study aims to analyze the effect of work facilities and training on employee performance with work motivation as a mediating variable. This study uses a quantitative approach with a census method on all 84 employees of the North Sumatra Provincial Narcotics Agency. Primary data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results show that work facilities and training have a positive and significant effect on employee performance and work motivation. In addition, work motivation was found to have a positive and significant effect on employee performance and was able to mediate the effect of work facilities and training on employee performance. These findings indicate that improving the quality of work facilities and training, supported by strengthening work motivation, is an important strategy in improving employee performance within the North Sumatra Provincial BNN. This study is expected to provide practical contributions to human resource management, particularly in the formulation of policies to improve the performance of public sector employees.